PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENILAIAN KINERJA PUSAT BIAYA PADA HOTEL SUTANRAJA AMURANG - Lopez, Paula da; Alexander, Stanly W.; Latjandu, Lady D. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
The succsess of a company can be measured through how management can design the right strategy as well as the implementation in the field to obtain the result. The use of responsibility accounting in a company can help in achieving this goal. Research conducted at Hotel Sutanraja Amurang with descriptive qualitative methods shows that this hotel has implemented responsibility accounting but has not been maximized, seen from the organizational structure, budget planning, account code classification, and accounting reporting. However, the classificitation of controlloed costs has not been included in the accountability report and there is no account code for this cost classification. The performance of the cost center atÂ  the Hotel Sutanraja Amurang has been considered quite good because it has acted in the planning process, as well as controlling the costs incurred